Genetic convergence of developmental and epileptic encephalopathies and intellectual disability. (11th July 2021) - Carvill, Gemma L; Jansen, Sandra; Lacroix, Amy; Zemel, Matthew; Mehaffey, Michele; De Vries, Petra; Brunner, Han G; Scheffer, Ingrid E; De Vries, Bert B A; Vissers, Lisenka E L M; Mefford, Heather C
Abstract : Aim: To determine whether genes that cause developmental and epileptic encephalopathies (DEEs) are more commonly implicated in intellectual disability with epilepsy as a comorbid feature than in intellectual disability only. Method: We performed targeted resequencing of 18 genes commonly implicated in DEEs in a cohort of 830 patients with intellectual disability (59% male) and 393 patients with DEEs (52% male). Results: We observed a significant enrichment of pathogenic/likely pathogenic variants in patients with epilepsy and intellectual disability (16 out of 159 in seven genes) compared with intellectual disability only (2 out of 671) ( p <1.86×10 −10, odds ratio 37.22, 95% confidence interval 8.60–337.0). Interpretation: We identified seven genes that are more likely to cause epilepsy and intellectual disability than intellectual disability only. Conversely, two genes, GRIN2B and SCN2A, can be implicated in intellectual disability without epilepsy; in these instances intellectual disability is not a secondary consequence of ongoing seizures but rather a primary cause. What this paper adds A subset of genes are more commonly implicated in epilepsy than other neurodevelopmental disorders. GRIN2B and SCN2A are implicated in intellectual disability and epilepsy independently. What this paper adds: A subset of genes are more commonly implicated in epilepsy than other neurodevelopmental disorders. GRIN2B and SCN2A are implicated in intellectual disability and epilepsy independently. This original article is commented by Specchio and Ferretti on page 1368 of this issue.